Jan Kochanowski, Elegiarum libri quattuor I 1: dall'imitatio testuale ad alcune considerazioni di critica del testo (Altre Modernità, 2015)
The purpose of this article is to analyse the Elegy I 1 from the Elegiarum libri quattuor Jana Kochanowskiego, both in the 1584 printed edition and in the manuscript version of Elegiarum libri duo, from the manuscrIpt Osmólski (1562-1564).The study also considers the epigrams Ad lectorem (introducing the elegies as well as the whole book) and the epigram Ad Myscovium, the proemial text of the collection of epigrams Foricoenia, printed in the same book, from the plainness of constant allusions – in the opening poems of Kochanowski – to particular texts, author, motifs (e.g., the author constantly refers to both satirical images and authors like Persius and Horace).In addition to the study of loci paralleli, especially focused on the presence of neolatin poetry in the elegy by Kochanowski, the article studies the way in which Kochanowski re-elaborated the elegy, preparing it for publication. From the manuscript to the edition of 1584 the poem did not undergo considerable modifications, as is the case of other elegies (el. II 3 = I 3 Osmólski). Kochanowski only wanted to give his work a higher degree of narrative coherence and to underline the meta-literary meaning of some images more strongly (e.g. the allusion to Horace’s Ars Poetica before the couplets on the Hercules labour).
Keywords: Kochanowski; Elegy; Neo Latin literature